A Comparative Analysis of School-Based Management in Central America - Di Gropello, Emanuela (World Bank, Washington, DC, 2012)
El Salvador, Guatemala, Honduras, and Nicaragua introduced education decentralization reforms, including school-based management (SBM) in some schools. As applied in Central America, (SBM) is a decentralization mechanism that shifts certain decision-making powers to the school level, emphasizing the role of community, and parental management in school affairs. The SBM programs aim to increase enrollments, efficiency, and parental and local community participation. Greater participations are also seen as a means to achieve other goals. In three cases-EDUCO (El Salvador), PRONADE (Guatemala), and PROHECO (Honduras)-the main objective is increasing enrollment in isolated rural areas affected by conflict, poverty, or natural disasters. The School Autonomy Program in Nicaragua aims to increase operational efficiency, by giving voice to parents and civil society on educational issues. The note discusses two key questions that arise: What effect have the reforms had on community empowerment, and educational outcomes? What can be learned by comparing the circumstances, reform designs, and contexts in the four countries?